Mycosis of the eye and its adnexa - Behrens-Baumann, Wolfgang (Developments in ophthalmology, 1999)
This volume presents the current knowledge on ocular mycology in its various diagnostic and therapeutic aspects. It is an extended translation of "Pilzerkrankungen des Auges" by the same author.The first chapter on general mycology is a contribution by R. Rüchel (Goettingen), and summarizes the relevant fungi and their classification. The following chapters describe antimycotic drugs including their systemic and topical administration, orbital infections such as mucor or aspergillosis together with their palpebral and lacrimal involvement. Data on conjunctival colonization keratomycosis, and its various diagnostic and therapeutic aspects are given, as well as information on endogenous endophthalmitis – risk factors, clinical presentation, medical and surgical therapy – together with the features of exogenous endophthalmitis. Ocular histoplasmosis syndrome and its differential diagnosis is discussed. In addition, the book presents case reports showing typical symptoms; comprehensive experimental data are provided in the final chapter. Ophthalmologists and general practitioners dealing with infectious diseases will find comprehensive and current data on pharmacokinetics, keratomycosis and endophthalmitis in this important publication